2006
DOI: 10.1080/17453670610012935
|View full text |Cite
|
Sign up to set email alerts
|

No difference in health-related quality of life in hip osteoarthritis compared to degenerative lumbar instability at pre- and 1-year postoperatively: A prospective study of 101 patients

Abstract: (2006) No difference in health-related quality of life in hip osteoarthritis compared to degenerative lumbar instability at pre-and 1-year postoperatively: A prospective study of 101 patients, Acta Orthopaedica, 77:5, 748-754, DOI: 10.1080 Background Total hip replacement (THR) is a very successful and refined surgical procedure when compared to crude bony fusion in degenerative lumbar segmental instability (LF). We compared the pre-and postoperative health-related quality of life status of THR and LF patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The functional outcome after 3 months in the THR group was in accordance with the results of other studies with a longer follow-up period (Bachmeier et al 2001, Juul et al 2006, Quintana et al 2005. This indicates that the main improvements after THR are seen rather early in late-phase rehabilitation.…”
Section: Discussionsupporting
confidence: 81%
“…The functional outcome after 3 months in the THR group was in accordance with the results of other studies with a longer follow-up period (Bachmeier et al 2001, Juul et al 2006, Quintana et al 2005. This indicates that the main improvements after THR are seen rather early in late-phase rehabilitation.…”
Section: Discussionsupporting
confidence: 81%
“…In a similar study, Juul et al [37] reported comparable improvements in SF-36 results at one year between patients who underwent hip arthroplasty and others treated with lumbar spinal fusion. Added to that, the group of patients who underwent hip arthroplasty displayed a higher improvement percentage than did the remaining cohorts that were intervened.…”
Section: Discussionmentioning
confidence: 77%
“…Previous research on mental health status in OA concentrated either on assessing mental health status before and after TJA [1116] [1722] or on evaluating how the presence of poor preoperative mental health or of depression impacted postoperative pain and function [7, 2325], [2628]. However, to the best of our knowledge, the relationship between degree of pain and function improvement and mental health improvement after THA has not been well studied.…”
Section: Introductionmentioning
confidence: 99%